A quinone electrode with reversible phase conversion for long-life rechargeable aqueous aluminum–metal batteries. Issue 56 (22nd June 2021) - He, Jinjun; Shi, Xin; Wang, Chengsheng; Zhang, Haozhe; Liu, Xiaoqing; Yang, Zujin; Lu, Xihong
Abstract : The implementation of tetrachloro-1, 4-benzoquinone (TCQ) as a high-energy cathode for aqueous aluminum–metal batteries is demonstrated for the first time, delivering a high capacity of 206.7 mA h g −1 and good cycling stability. Abstract : The exploration of high-performance cathode candidates is of great significance for aqueous aluminum–metal batteries (AAMBs). Here, we, for the first time, report tetrachloro-1, 4-benzoquinone (TCQ) as a superior organic AAMB cathode. Owing to its high reversible conversion between the carbonyl and hydroxyl groups, the TCQ cathode delivers a remarkable electrochemical performance.